Cancer in the electric power industry. Issue 3 (March 1986) - Törnqvist, S; Norell, S; Ahlbom, A; Knave, B
Abstract : A cohort study of 3358 power linesmen and 6703 power station operators classified in the 1960 population census in Sweden was undertaken. The cancer incidence between 1961 and 1979 was calculated in relation to all male blue collar workers. The relative risk of cancer (all sites) was 1.1, (1.0-1.2, 90% confidence limit) in the group of power linesmen and 1.0 (0.9-1.0) for power station operators. No consistent excess risk of leukaemia or brain tumour was found in the two occupational groups. In both groups a tendency towards an excess risk of cancer of the urinary organs was found.